Structure of the Seagrass Community in Meras Beach, Bunaken District, Manado City, North Sulawesi - Manurung, Nia Dopa; Kondoy, Khristin; Rondonuwu, Ari B.; Wantasen, Adnan; Mantiri, Rose O. S. E.; Manengkey, Hermanto (Sam Ratulangi University, 2022)
Seagrass is a flowering plant (Angiospermae) that grows and breeds on the bottom of shallow sea waters, from tidal areas (intertidal zone) to sublittoral areas. The role of seagrass in shallow marine waters is as a primary producer, as a habitat for biota, catching sediments, and a nutrient recycler. The existence of seagrass is influenced by several factors, namely: temperature, salinity, depth, brightness, nutrients, and salinity. The purpose of this study was to determine the Relative Density, Relative Abundance, Relative Dominance, Frequency, Relative Frequency, Important Value Index, Diversity Index, and Dominance Index, to determine the types of seagrass and to determine the condition of the aquatic environment. This research uses the quadratic methods and line transect. This research was conducted on May 28, 2021, at Meras Beach, Bunaken District, Manado City, North Sulawesi. The number of stands of seagrass species in the study area ranged from 23-320 individuals, species density (8.36-116.36 individuals/m2), relative density (3.62-50.47%), frequency of presence (0.037- 0.50 ), relative frequency (3.62- 50.47%), dominance index (0.072-1.009), the diversity index (1.236), index of the importance of seagrass in Meras Coastal Waters showed that Cymodocea rotundata had the highest important value index among the 5 seagrass species, namely 151.41%. There are 5 species of seagrass found in Meras Coastal Waters, namely, Enhalus acoroides, Syringodium isoetifolium, Halophila ovalis, Cymodocea rotundata, Thalassia hemprichii. The environmental conditions in Meras Beach are temperature 29°C, salinity 35‰, the brightness is quite clear and has a substrate of sand, muddy, sand mixed with mud, muddy mixed with sand, and coral fragments.Keywords: Meras Beach; Seagrass; Community Structure.AbstrakLamun (seagrass) adalah tumbuhan berbunga (Angiospermae) yang tumbuh dan berkembang biak pada dasar perairan laut dangkal, mulai daerah pasang surut (zona intertidal) sampai dengan daerah sublitoral. Peranan lamun di lingkungan perairan laut dangkal sebagai produsen primer, sebagai habitat biota, penangkapan sedimen dan sebagai pendaur zat hara. Keberadaan lamun dipengaruhi oleh beberapa faktor yaitu: suhu, salinitas, kedalaman, kecerahan, nutrient dan salinitas. Tujuan penelitian ini adalah untuk mengetahui Kepadatan Relatif, Kelimpahan Relatif, Dominasi Relatif, frekuensi, Frekuensi Relatif, Indeks Nilai Penting, Indeks Keanekaragaman, dan Indeks Dominasi, untuk mengetahui jenis-jenis lamun dan untuk mengetahui bagaimana kondisi lingkungan perairan. Adapun penelitian ini menggunakan metode kuadrat dan line transek. Penelitian ini dilaksanakan pada tanggal 28 Mei 2021, dilakukan di Pantai Meras, Kecamatan Bunaken, Kota Manado, Sulawesi Utara. Jumlah tegakan spesies lamun di lokasi penelitian berkisar dari 23-320 individu, kepadatan spesies (8,36-116,36 individu/m2), kepadatan relatif (3,62- 50,47%), frekuensi kehadiran (0,037- 0,50) , frekuensi relatif (3,62- 50,47%), indeks dominasi (0,072-1,009), indeks keanekaragaman (1,236), indeks nilai penting lamun di Perairan Pantai Meras menunjukkan bahwa Cymodocea rotundata memiliki indeks nilai penting paling tinggi diantara ke 5 spesies lamun yakni 151, 41 %). Spesies lamun yang ditemukan di Perairan Pantai Meras berjumlah 5 yaitu, Enhalus acoroides, Syringodium isoetifolium, Halophila ovalis, Cymodocea rotundata, Thalassia hemprichii. Kondisi lingkungan di Perairan Pantai Meras yakni suhu 29°C, salinitas 35‰, kecerahan cukup jernih dan memiliki substrat pasir, berlumpur, pasir bercampur lumpur, berlumpur campur pasir dan pecahan karang. Kata kunci: Pantai Meras; Lamun; Struktur Komunitas.